Recent Developments on Using Nanomaterials to Combat Candida albicans - Li, Bingxin; Pan, Luyao; Zhang, Haofeng; Xie, Lingping; Wang, Xi; Shou, Jiahui; Qi, Yu; Yan, Xiaojian (Frontiers in Chemistry, 2021)
Vaginal candidiasis (VC) is a common disease of women and the main pathogen is Candida albicans (C. albicans). C. albicans infection incidence especially its drug resistance have become a global health threat due to the existence of C. albicans biofilms and the low bioavailability of traditional antifungal drugs. In recent years, nanomaterials have made great progresses in the field of antifungal applications. Some researchers have treated fungal infections with Inorganic nanoparticles, represented by silver nanoparticles (AgNPs) with antifungal properties. Liposomes, polymeric nanoparticles, metal-organic frameworks (MOFs), and covalent organic frameworks (COFs) were also used to improve the bioavailability of antifungal drugs. Herein, we briefly introduced the recent developments on using above nanomaterials to combat C. albicans in antifungal applications.